Proceedings of the National Workshop on Experience Sharing in Landscape Restoration Research implemented by Higher Learning Institutions (HLIs) in Ethiopia - Adimassu, Zenebe; Belay, Berhanu; Tamene, Lulseged D.; Tibebe, Degefie; Abera, Wuletawu (2024)
Ethiopian public universities and research organizations are actively engaging in landscape restoration efforts to fulfill their community engagement responsibilities. However, challenges exist as restoration practices are not coordinated, data collection and monitoring are inconsistent, and research findings are not effectively shared or documented. There is a lack of advocacy for landscape restoration among stakeholders, necessitating the establishment of a platform for knowledge exchange. The Alliance of Bioversity International, CIAT, and AICCRA organized a workshop to facilitate experience sharing among higher learning institutions, aiming to synergize efforts and scale up successful practices to contribute to national restoration initiatives. Ethiopian higher learning institutions have made significant progress in land restoration projects, showcasing their commitment to environmental sustainability and biodiversity enhancement. The preliminary results and achievements highlighted during the workshop demonstrate the impactful work being done by these institutions. By analyzing and publishing these results, valuable insights can be shared with end users, contributing to broader knowledge dissemination and potentially inspiring further landscape restoration initiatives in the country. Landscape restoration in higher learning institutions (HLIs) in Ethiopia presents a unique opportunity to address environmental challenges while enhancing educational experiences. In Ethiopia, HLIs can play a pivotal role in restoring degraded landscapes, conserving biodiversity, and promoting sustainable land management practices. By integrating native plant species, water-efficient landscaping, and eco-friendly infrastructure development, these institutions can create green spaces that serve as outdoor classrooms for students and research hubs for faculty. Engaging the community in restoration initiatives can also foster environmental awareness and contribute to broader conservation efforts in the country. Overall, landscape restoration in Ethiopian HLIs offers a holistic approach to environmental stewardship, innovation, and knowledge sharing within the academic community and beyond.